PERBAIKAN PRODUKSI GULA SEMUT UKM MAMA GARDEN DENGAN APLIKASI MESIN PENGERING DAN MESIN PENGHALUS (DISK MILL) - Mariam, .; Hasniar, .; Mustafa, Arnida (Jurnal Dinamika Pengabdian, 2020)
Sugar palm (Arenga pinnata Merr.) is a type of palm that has the potential for high economic value, producing palm sugar. So far, farmers in Barugae village have only used the technique of making brown sugar blocks from generation to generation, which only costs IDR.15,000 per kg. One of the SMEs in Barugae village that has implemented the production process of making brown sugar in powder form or better known as ant sugar is Mama Garden. This SME is located in Barugae Village, Bulukumpa District, Bulukumba Regency. The problem faced by the Mama Garden SME is the production process that still uses manual techniques, resulting in low quality products, drying using sunlight so it is very dependent on nature. Based on this, the Community service program implemented science and technology that could improve quality and increase the production capacity of the Mama Gaden SME. Improvements in the processing process include the use of flour machines and the use of dryers as well as the application of CPPOB, sanitary and hygienic aspects; shelf life (expiry date) of the ant sugar products; production management, and separate financial reports. The targets and outputs that have been achieved are quality improvement and additional production capacity, increased application of science and technology in society, and products in the form of sugar ant. Other outputs in the form of publications in mass media have been published, publications in scientific journals published in September 2020 in the community service journal of Jurnal Dinamika Pengabdian and activity videos that have been uploaded on YouTube.   Keywords: Brown sugar, ant sugar, packaging, processing.   ABSTRAK Aren (Arenga pinnata Merr.) adalah jenis palma yang memiliki potensi nilai ekonomi yang tinggi, penghasil gula aren. Selama ini petani di desa Barugae hanya menggunakan teknik pembuatan gula merah cetak secara turun temurun yaitu membuat gula merah cetak yang harganya berada pada harga Rp. 15.000 per kg. Salah satu UKM yang berada didesa barugae yang telah menerapkan proses produksi pembuatan gula merah dalam bentuk serbuk atau yang lebih dikenal dengan nama gula semut adalah Mama garden. UKM ini berada di Desa Barugae Kecamatan Bulukumpa Kabupaten Bulukumba. Permasalahan yang dihadapi oleh UKM Mama Garden adalah proses produksi yang masih menggunakan teknik manual, sehingga produk yang dihasilkan memiliki kualitas rendah, pengeringan dengan menggunakan sinar matahari sehingga sangat tergantung pada alam. Berdasarkan hal tersebut maka pada program PKM ini dilakukan penerapan iptek yang dapat meningkatkan kualitas serta menambah kapasitas produksi mama gaden. Perbaikan proses pengolahan yang dimaksud diantaranya adalah penggunaan mesin penepung, dan penggunaan pengering serta penerapan aspek CPPOB, aspek sanitasi dan hygienis, masa simpan (expiry date) dari produk gula semut, manajemen produksi, dan laporan keuangan tersendiri. Target dan luaran yang telah dicapai adalah perbaikan kualitas dan penambahan kapasitas produksi, peningkatan penerapan iptek di masyarakat, dan produk berupa gula semut yang dihasilkan. luaran lain berupa publikasi pada media massa dan jurnal ilmiah di Jurnal Dinamika Pengabdian dan video kegiatan yang telah diupload di youtube.   Kata Kunci: Gula merah, gula semut, pengemasan, pengolahan.